2020
DOI: 10.1016/j.cognition.2020.104322
|View full text |Cite
|
Sign up to set email alerts
|

The impact of false denials on forgetting and false memory

Abstract: People sometimes falsely deny having experienced an event. In the current experiments, we examined the effect of false denials on forgetting and false memory formation. In Experiment 1, participants were presented with emotionally-negative and neutral associatively related word lists known to engender false memories. After encoding, half of the participants had to falsely deny having seen the words while the other half had to tell the truth. During a final memory test (recall or source monitoring task), partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 45 publications
5
46
1
Order By: Relevance
“…People often deny the events or details of events that occur in daily life. Some studies have demonstrated that false denial could disrupt liar's memories and lead to the loss of memory about what they have lied about (Otgaar et al, 2018a(Otgaar et al, , 2020Battista et al, 2020aBattista et al, , 2021a, and this phenomenon is called the DIF effect (Otgaar et al, 2016). However, several studies have failed to obtain such an effect (Romeo et al, 2019b;Li et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…People often deny the events or details of events that occur in daily life. Some studies have demonstrated that false denial could disrupt liar's memories and lead to the loss of memory about what they have lied about (Otgaar et al, 2018a(Otgaar et al, , 2020Battista et al, 2020aBattista et al, , 2021a, and this phenomenon is called the DIF effect (Otgaar et al, 2016). However, several studies have failed to obtain such an effect (Romeo et al, 2019b;Li et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Lying can have negative consequences, especially for the liar's memory. A wealth of studies have consistently demonstrated that liars' memories can be disrupted by their lies (Otgaar et al, 2014a(Otgaar et al, , 2018a(Otgaar et al, , 2020Romeo et al, 2019b;Battista et al, 2020aBattista et al, , 2021a. People might forget some details of events that they have lied about (Otgaar et al, 2018a;Romeo et al, 2019b;Battista et al, 2020a), and they may also forget what they lied about during an interview (Battista et al, 2020a,b;Battista et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first study of false denial, Vieira and Lane (2013) , using a within-subject design, found false denial to cause poor memory of the studied items compared to telling the truth. Studies using a between-subject design have also found that participants engaged in false denial make more omission errors than those who are truthful ( Otgaar et al, 2016a , 2018 , 2020 ; Romeo et al, 2019a ; Battista et al, 2021a ). Interestingly, previous studies have reported that false denial also results in worse performance on source memory tests relative to honest responses, suggesting that participants who deceive lose more memories about what they lied about ( Otgaar et al, 2014a , 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…All the findings observed in these studies were statistically significant and, specifically, demonstrated that overall lying on an event leads to a detrimental effect on memory. Finally, when we looked at the limitations stated by the authors in their papers, almost all the scholars indicated as a principal issue the impossibility to completely generalize the findings in real situations due to several reasons ( Pezdek et al, 2007 ; Vieira and Lane, 2013 ; McWilliams et al, 2014 ; Harvey et al, 2017a , b ; Besken, 2018 ; Mangiulli et al, 2018 , 2019a , b ; Otgaar et al, 2018 , 2020 ; Battista et al, 2020 , 2021a ; Riesthuis et al, 2020 ; Li and Liu, 2021 ; Vo et al, 2021 ). In particular, the main reasons reported to explain this issue were (i) the use of a sample of the population (i.e., students) being not necessarily representative of the general population (ii) the stimulus adopted lacking of ecological validity.…”
Section: Discussionmentioning
confidence: 98%